Risk factors for COVID-19 infections among health care workers in Ghana. - Margaret Lartey; Ernest Kenu; Vincent Jessey Ganu; Franklin Asiedu-Bekoe; Baafour Kofi Opoku; Alfred Yawson; Sally-Ann Ohene (PLoS ONE, 2023)
Introduction Health care workers (HCWs) are crucial to the fight against COVID-19 and are at risk of being infected. We sought to determine the risk factors and associations of COVID-19 among HCWs in Ghana during the period of the pandemic. Materials and methods A case-control study was conducted using the WHO COVID-19 HCWs exposure risk assessment tool. A HCW was categorized as "high risk" for COVID-19 if s/he did not respond "always, as recommended" to adherence to Infection Prevention and Control (IPC) measures during a healthcare interaction. A HCW was categorized as "low risk" if s/he responded "always, as recommended" to adherence to IPC measures. We used univariate and multiple logistic regression models to determine associated risk factors. Statistical significance was set at 5%. Results A total of 2402 HCWs were recruited and the mean age was 33.2±7.1 years. Almost 87% (1525/1745) of HCWs had high risk for COVID-19 infection. Risk factors identified were profession (doctor- aOR: 2.13, 95%CI: 1.54-2.94; radiographer-aOR: 1.16, 95% CI: 0.44-3.09)), presence of comorbidity (aOR: 1.89, 95%CI: 1.29-2.78), community exposure to virus (aOR: 1.26, 95% CI: 1.03-1.55), not performing hand hygiene before and after aseptic procedures performed (aOR: 1.6, 95% CI: 1.05-2.45); not frequently decontaminating high-touch surfaces always as recommended (aOR: 2.31, 95%CI: 1.65-3.22; p = 0.001) and contact with a confirmed COVID-19 patient (aOR: 1.39, 95% CI: 1.15-1.67). Among those who came into any form of contact with confirmed COVID-19 patient, providing direct care (aOR: 2.0, 95%CI: 1.36-2.94), face-to-face contact (aOR: 2.23, 95%CI: 1.41-3.51), contact with environment/materials used by COVID-19 patient (aOR: 2.25, 95%CI: 1.45-3.49) and presence during conduct of aerosol generating procedures (aOR: 2.73, 95%CI: 1.74-4.28) were associated with COVID-19 infection. Conclusion Non-adherence to IPC guidelines puts HCWs at increased risk of COVID-19 infection thus ensuring IPC adherence is key to reducing this risk.